PARENTING STYLES IN NICOLA YOON’S NOVEL EVERYTHING, EVERYTHING - Ade Rahmad Kurnia; Asnani Asnani (JOURNAL OF LANGUAGE, 2022)
This study is entitled "Parenting Style in Nicola Yoon's Novel Everything, Everything". This study focuses on the type of parenting style applied by Pauline Whittier to her daughter, Madeline Whittier, who suffers from SCID (Severe Combined Immuno-Deficiancy).  There are two objectives of this research, namely to find out the types of parenting styles and to describe how the parenting styles are implemented in Nicola Yoon's novel Everything, Everything. The researchers uses the Parenting style theory proposed by Diana Baumrind. The data were collected through literature study and the researchers found twelve data that could be used as data analysis. The researchers used qualitative research method to analyze the data. Based on the results of the analysis, the researchers came to two conclusions. First, the type of parenting style in the novel Everything, Everything by Nichola Yoon is Authoritarian Parenting style. This style is applied by Pauline to her daughter Madeline. Secondly, Based on the analysis, Pauline's parenting style has four characteristics, namely strict discipline, one-way communication, order without negotiation and giving punishment.